2009
DOI: 10.1073/pnas.0901594106
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiations: From field to genomic studies

Abstract: Adaptive radiations were central to Darwin's formation of his theory of natural selection, and today they are still the centerpiece for many studies of adaptation and speciation. Here, we review the advantages of adaptive radiations, especially recent ones, for detecting evolutionary trends and the genetic dissection of adaptive traits. We focus on Aquilegia as a primary example of these advantages and highlight progress in understanding the genetic basis of flower color. Phylogenetic analysis of Aquilegia ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 84 publications
1
80
0
Order By: Relevance
“…These recently by taxon, reflecting independent and relatively recent diversified species have long fascinated researchers gene duplications (Nam et al, 2004;Arora et al, working in the fields of evolution and ecology due to 2007). Second, they are commonly involved in the their association of poor genetic differentiation with development of the female gametophyte and endo-highly divergent pollinator syndromes (Hodges et al, sperm, as confirmed by both forward genetics and 2004; Hodges & Derieg, 2009). More recently, broad expression studies (Bemer et al, 2010b and Aquilegia has become a model for the evolution of references therein).…”
mentioning
confidence: 99%
“…These recently by taxon, reflecting independent and relatively recent diversified species have long fascinated researchers gene duplications (Nam et al, 2004;Arora et al, working in the fields of evolution and ecology due to 2007). Second, they are commonly involved in the their association of poor genetic differentiation with development of the female gametophyte and endo-highly divergent pollinator syndromes (Hodges et al, sperm, as confirmed by both forward genetics and 2004; Hodges & Derieg, 2009). More recently, broad expression studies (Bemer et al, 2010b and Aquilegia has become a model for the evolution of references therein).…”
mentioning
confidence: 99%
“…For example, flower colour is a trait with astonishing lability over evolutionary time and the potential to discriminate between pollinator types. Multiple evolutionary shifts from hummingbird to moth pollination in Aquilegia have been associated with independent losses of anthocyanin production [37]. The molecular basis of many such shifts is attributable to changes in the transcription factors that regulate the pigment synthetic pathway (reviewed by [38]), and similar changes can cause variations in the pattern of floral pigment, generating spots, veins and other nectar guides that are differentially used by different pollinators [39,40*,41].…”
Section: Pollinators and Crop Productionmentioning
confidence: 99%
“…One biological process that can lead to the evolution of such diverse groups is adaptive radiation. Adaptive radiation refers to the rapid diversification of an ancestral species, producing descendants adapted to a great variety of ecological niches (Gavrilets & Losos 2009;Hodges & Derieg 2009;Losos 2010;. Adaptive radiations can result either from ecological opportunity, where an ancestral species colonizes an environment with underutilized resources like under populated lakes or islands, or from "key innovations" allowing the establishment of novel ways to interact with the environment .…”
Section: S Lautus Has Adapted Repeatedly To Coastal Environmentsmentioning
confidence: 99%
“…have not yet fully attained RI are especially profitable resources for dissecting the genetic basis of ecological speciation, because they allow to test the effect of gene flow in speciation and because the ability to make hybrids allows the dissection of the genetic basis of traits (Hodges & Derieg 2009). Additionally, adaptive radiations presenting a diversity of adaptive traits or the repeated evolution of the same traits in different lineages constitute excellent systems for identifying evolutionary trends and estimating whether evolution follows predictable trajectories (Hodges & Derieg 2009 , some environments seem to have been colonized repeatedly as S. lautus populations are grouped according to their geographic location independently of their ecology and morphology.…”
Section: S Lautus Has Adapted Repeatedly To Coastal Environmentsmentioning
confidence: 99%
See 1 more Smart Citation